Relationship between ovarian ultrasonographic findings on the seventh post-estrus day and plasma progesterone concentration, nutritional metabolic factors, and pregnancy outcome in dairy cows - Naoya KAWAHARA; Yoshiyuki TSUCHIYA; Natsumi ENDO; Tomomi TANAKA (The Society for Reproduction and Development, 2022)
To improve the accuracy of ultrasonographic assessment of luteal function, we investigated the relationship between ovarian ultrasonographic findings on Day 7 (Day 1 = ovulation) and plasma progesterone (P4) concentration, nutritional metabolic factors, and pregnancy outcome. A total of 47 spontaneous estrus events were investigated in 38 lactating Holstein cows (artificial insemination, n = 31; embryo transfer, n = 16). Transrectal ultrasonography was performed on Days 0 and 7 to measure the pre-ovulatory follicle area on Day 0 and the luteal tissue area (LTA), luteal blood flow area (LBF), relative LBF (rLBF) (= LBF/LTA), and dominant follicle area (DFA) on Day 7. Blood samples were collected on Day 7 to measure plasma P4, insulin-like growth factor-I (IGF-I), insulin, and metabolites. Plasma P4 concentration was positively correlated with LTA but was not associated with LBF or rLBF. Plasma P4 concentration was positively correlated with blood glucose and IGF-I and negatively correlated with blood urea nitrogen and free fatty acid, and no significant relationship was found between the ultrasonographic findings of the corpus luteum (CL) and these blood metabolites. Pregnant cows had smaller DFA than non-pregnant cows. In conclusion, LTA measurement can help predict plasma P4 concentration, but it was difficult to detect variations in plasma P4 concentration in relation to changes in energy status by evaluating the CL ultrasonographically. A combined assessment of CL and first-wave dominant follicle may be important in evaluating fertility.